Efektivitas Penggunaan Controlled Droplet Application pada Penyemprotan Gulma di Perkebunan Kelapa Sawit - Toto Suryanto; Edo Vernando; Jojon Soesatrijo (Politeknik Kelapa Sawit Citra Widya Edukasi, 2022)
Controlled Droplet Application (CDA) is a herbicide spraying tool that uses a battery dynamo power and a disc-shaped nozzle, which can dispense a more even spray solution. Spraying activities will also be completed faster with high work performance. The purpose of this study was to determine the effectiveness and efficiency of the knapsack sprayer and CDA, as well as the mortality rate of weeds after the application of the two tools. Parameters observed were spraying time, work performance, weed mortality rate and cost comparison. The results showed that the CDA sprayer was more effective in controlling weeds, because it was able to spray an area of ??1381.6 m2/tank and was also more efficient at a cost of Rp. 53,508/ha. Meanwhile, the knapsack sprayer is capable of spraying an area of ??188.4 m2/tank at a cost of Rp 89,436/ha. Weed mortality rate after herbicide application with CDA sprayer reached 99%, whereas with knapsack sprayer it only reached 90%.